The Influence of Lifestyle and Belief on Purchasing Decisions using the Shopee Paylater featur among INSURI Ponorogo Student - Supiyah, Ririn; Fikriawan, Suad; Wahyudi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aim to determine the influence of lifestyle and beliefs on purchasing decisions using the Shopee Paylater feature among INSURI Ponorogo students. This type of research is descriptive research using a quantitative approach, with data collection procedures through questionnaire and observation techniques. In this study, the population used was INSURI Ponorogo students using a purposive sampling technique which is included in the non-probability sampling technique. The sample in this study was 100 students. The analysis used is multiple linear regression analysis. Multiple linear regression calculations in this research used the Eviews-10 program. The research results show that lifestyle has no partial effect, trust has a partial effect, and lifestyle and trust have a simultaneous effect on purchasing decisions using the Shopee Paylater feature among INSURI Ponorogo students.